2021
DOI: 10.1089/tmj.2020.0386
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Opportunities in the COVID-19 Pandemic Early Days: What Happened, Did Not Happen, Should Have Happened, and Must Happen in the Near Future?

Abstract: The objective of this communication is to offer a better understanding of the value of telemedicine in health care, particularly its role in creating opportunities for continuity of care to patients in a complex and novel setting as were the circumstances of the early COVID-19 pandemic times. Crisis time is also a time for opportunities. With regard to telehealth, all players (providers, staff, and patients) should be informed about its benefits and should also become familiar with the use of the various teleh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 10 publications
0
17
0
3
Order By: Relevance
“…It is important to help patients, in particular chronic patients, to take responsibility for their own health status and self-care. 27 The patient and the nurse, together, can identify symptoms as well as manage the physical, emotional, and social impact of the disease, leading to an improved quality of life. In this COVID-19 pandemic, it is important to accelerate the training of patients and caregivers on how to care for this specific disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to help patients, in particular chronic patients, to take responsibility for their own health status and self-care. 27 The patient and the nurse, together, can identify symptoms as well as manage the physical, emotional, and social impact of the disease, leading to an improved quality of life. In this COVID-19 pandemic, it is important to accelerate the training of patients and caregivers on how to care for this specific disease.…”
Section: Discussionmentioning
confidence: 99%
“…Such results highlight gaps towards how well integrated care is promoted in telehealth and suggest a need to better support patient participation in their health care (Thomas et al , 2020). Indeed, when patients are adequately prepared and educated towards self-management and computer literacy, then telehealth has the potential to empower them in managing their health (Amorim et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“… 79 In many cases, the radical change in practice had to happen without much of the needed preparation or advanced planning. 80 Despite this almost overnight transformation, there are reports that allergic patients' satisfaction with telemedicine during the pandemic was high. A recent study conducted in a Spanish allergy unit, demonstrated that half of the patients that underwent a telephone consultation during the first peak of the pandemic would welcome this practice after the resolution of the epidemiological emergency.…”
Section: Ehealth For Patients and Patient Representativesmentioning
confidence: 99%
“…The most heavily affected countries saw their allergy practices rapidly being converted to telemedicine within days 79 . In many cases, the radical change in practice had to happen without much of the needed preparation or advanced planning 80 . Despite this almost overnight transformation, there are reports that allergic patients' satisfaction with telemedicine during the pandemic was high.…”
Section: Ehealth For Patients and Patient Representativesmentioning
confidence: 99%